One-pot biocatalyzed preparation of substituted amides as intermediates of pharmaceuticals - Baldessari, Alicia (2001)
A lipase-catalyzed procedure is described for the one-pot conversion of carboxylic acids into substituted amides via in-situ formation of the ethyl ester and subsequent aminolysis. The procedure was optimized for the preparation of tetrahydro-N-[3-(methylamino)-propyl]-2-furancarboxamide, an intermediate in the synthesis of Alfuzosin, a reducing agent of symptoms associated with benign prostatic hypertrophy. This methodology proved to be general and can be applied to open-chain, cyclic, hydroxy-, amino-, dicarboxylic, various chain lengths, and unsaturated acids. Moreover, the enzyme shows a regioselective behavior in relation to primary and secondary amino groups. The procedure involved the treatment of the corresponding carboxylic acid with ethyl alcohol in presence of immobilized Candida antarctica lipase followed by addition of amine. The amide is obtained in good yields and regioselective way.